2015
DOI: 10.1090/tran/6659
|View full text |Cite
|
Sign up to set email alerts
|

Vapnik-Chervonenkis density in some theories without the independence property, I

Abstract: We recast the problem of calculating Vapnik-Chervonenkis (VC) density into one of counting types, and thereby calculate bounds (often optimal) on the VC density for some weakly o-minimal, weakly quasi-o-minimal, and P -minimal theories.Our approach to Theorem 1.1, via definable types, was partly inspired by the use of Puiseux series in [11,81].Let ACVF denote the theory of (non-trivially) valued algebraically closed fields, in the ring language expanded by a predicate for the valuation divisibility. This has c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(109 citation statements)
references
References 90 publications
(139 reference statements)
2
107
0
Order By: Relevance
“…For the sake of completeness, before stating the main result of the section we briefly recall the definition of vc-density. We refer the reader to [3] for a detailed exposition.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…For the sake of completeness, before stating the main result of the section we briefly recall the definition of vc-density. We refer the reader to [3] for a detailed exposition.…”
Section: 2mentioning
confidence: 99%
“…The vc-density has been studied for quite some time in combinatorics, computational geometry, statistics and machine learning. In model theory it relates to the classical problem of counting types and was furthermore studied extensively in many specific cases in [3,2].…”
Section: Introductionmentioning
confidence: 99%
“…At the intersection of CLT and classical model theory is the concept of VC dimension (Aschenbrenner, Dolich, Haskell, Macpherson, & Starchenko, 2011, 2013Kearns and Vazirani, 1994;Laskowski, 1992), which we mentioned briefly. It could be possible to reconcile the results of these two disciplines in E-and F-logics, to the benefit of all involved.…”
Section: Classical Model-theory Techniquesmentioning
confidence: 99%
“…A number of results were proved about the inexistance of such expansions. In [3] it was shown that (Z, +, 0, 1, <) has no proper dp-minimal expansions. This was later significantly strengthened in [7] by the following: Fact 1.1 ([7,Corollary 2.20]).…”
Section: Introductionmentioning
confidence: 99%